Balancing individual choice and Islamic principles: the childfree lifestyle through the lens of Maqasid al-Shariah - Mat Jubri @ Shamsuddin, Mustafa (Penerbit UniSIRAJ, 2024)
The growing trend of voluntary childlessness in Muslim communities has sparked debates on its compatibility with Islamic principles, particularly the Maqasid al-Shariah's emphasis on preservation of progeny. This research explores the tensions between individual reproductive choices and traditional Islamic teachings, aiming to provide a nuanced understanding of the childfree lifestyle through the framework of Maqasid al-Shariah. The study employs a qualitative methodology, focusing on library research and analysis of Islamic texts, contemporary fatwas, and scholarly works. Findings reveal a gradual shift in Islamic scholarly discourse towards more nuanced interpretations of the concept of lineage preservation (hifz al-nasl) that consider societal contribution beyond procreation. The research develops a decision-making framework that balances potential benefits (maslahah) and harms (mafsadah) of childfree choices, considering factors such as necessity, scope of impact, and individual circumstances. While the study acknowledges the validity of childfree choices in certain contexts, it also highlights the ongoing tensions with traditional Islamic views on family formation. This research contributes to the evolving discourse on Islamic bioethics and family planning, potentially informing religious guidance and social policies in Muslim-majority countries.